MODEL PENGEMBANGAN KAMPUS TEMATIK DALAM KAWASAN AGROTEKNO PARK - BambangSoemardiono; Iwan Adi Indrawan; Nurfahmi Muchlis (Talenta Publisher, 2019)
The Agro Techno Park area in North Gresik is a proposal developed by the local government with master plan design concepts with a theme that combines industry and campus based on education and research (Erica Campus). With strong potential supported by infrastructure plans for the development of north Gresik, this area has the potential to be developed. Research problems that arise are aspects of what aspects need to be considered in structuring these thematic clusters and how the criteria that help strengthen campus development planning concepts in the long term. Hanyang University is one example of the Erica campus cluster in south Korea that applies new standards and is recognized as a school that actively collaborates with industry. This cluster must have a strong and specific peculiarity because it is in the agro-industrial region so that in its footprint other than the mass, circulation and open space. There are special needs that need to be studied in depth so that the concept of merging is achieved to develop conceptual directives in the form of thematic campus development models